Secure IT Systems 20th Nordic Conference, NordSec 2015, Stockholm, Sweden, October 19-21, 2015, Proceedings - Buchegger, Sonja; Dam, Mads (Security and Cryptology, 2015)
This book constitutes the proceedings of the 20th Nordic Conference on Secure IT Systems, held in Stockholm, Sweden, in October 2015. The 11 full papers presented together with 5 short papers in this volume were carefully reviewed and selected from 38 submissions. They are organized in topical sections named: cyber-physical systems security, privacy, cryptography, trust and fraud, and network and software security.